Social sciences in sport - Maguire, Joseph A. 1956- (Human Kinetics, 2014)
Social Sciences in Sport presents discipline-specific knowledge in the social sciences, which aids in understanding the problems and potential of contemporary sport practices and experiences. This interdisciplinary reference provides in-depth coverage of sport studies and 14 social sciences, drawing connections across these disciplines to illuminate key issues and illustrate possibilities for change. Written by leading figures in the social sciences, the book synthesizes theory and research in social science and sport into four distinct areas: Identity, which discusses individual development and ethical considerations from history, philosophy, and psychology; Community, which considers anthropology, sociology, geography, and media studies when looking at sport in social groups; Capital, which draws research in status, wealth, power, and resources from economics, political science, and international relations; Governance, which discusses the enhancement of sport through law, social policy, management studies, and education; Organized around these topics into four parts, this reference places sport in the broader social sciences, showing where researchers in kinesiology and other disciplines can augment their knowledge base. Noting the range of issues and concerns in today's sport environment, readers will analyze the potential of a human development model in sport studies. Editor Joseph Maguire and an esteemed team of contributors present the evolution of sport in various social sciences. A stage-setting introduction explains the relevance of a social scientific perspective on sport and physical activity, and part introductions outline many relationships between the social sciences and sport. Chapters include a historical overview of the discipline or subject area, the core concepts and main theoretical perspectives in that area of expertise, critical findings, and the contemporary debates that characterize sport. Equipped with the social scientific knowledge and new perspectives from this essential collection, students and practitioners will be able to navigate classic and emerging issues in sport. Whether readers are social scientists considering sport as a subject of study or sport studies scholars attempting to make connections with the broader disciplines, Social Sciences in Sport promotes development of and through sport